Overview of geographical conditions and natural resources of fifty islands on the Bac Bo coastline of Vietnam - Khanh, Uong Dinh; An, Le Duc; Tuan, Tong Phuc; Nga, Tran Thi Hang; Dung, Bui Quang; Huong, Nguyen Thi (Vietnam Journal of Earth Sciences, 2014)
50 islands (with area ≥ 1 km2) of the Bac Bo coastline are distributed into 3 lines extended from the North West-South East covering the continent. The islands have a natural conditions and rich natural resources of non-living (mineral resources, geological heritage, value-geomorphology, touristic resources,...) and biological resources (national parks, biosphere reserves, marine protected area planning and diversity of plant and animal species, etc.). There is tremendous potential for economic and social development of the Bac Bo region, as well as playing an important role in protecting the security, defense and sovereignty of Vietnam.